GOING AGAINST THE GRAIN: REIMAGINING THE ROLE OF HIGH SCHOOL PRINCIPALS AND PRINCIPAL SUPERVISOR AS ADAPTIVE LEADERS - Hernandez, Janette (East Carolina University, 2019)
To create conditions for high school principals and the principal supervisor to successfully lead career-themed pathways, a principal supervisor established a Community of Practice (CoP) and differentiated equity-focused coaching for principals so they could deeply engage in leading the implementation of high school small learning communities. Through the use of a participatory action research (PAR) methodology that included the principals as co-practitioner researchers (CPR), the study examines how the principals and principal supervisor remained focused on the larger vision and goal of leading schools with intentionality and instructional focus. By purposefully identifying adaptive challenges, using community learning exchange pedagogies and ensuring a robust planning and implementation process for students, the principals were able to concentrate on joint work and recognize how to apply the adaptive leadership framework to their challenges. The participatory action research process provided guidelines for collecting and analyzing the qualitative data to construct theories grounded in the data that led to these three claims: (1) Interrupting typical district supervisory-principal relations requires going against the grain of typical district practice; (2) the adaptive leadership framework provided a metacognitive and meta-affective framework that was useful, but insufficient, in principals fully transferring their reflection to school leadership practice; and (3) living with the tension of the dual role of evaluator and supporter, the district supervisor has to blend professional capital with professional accountability to achieve a balanced approach to supervising and coaching. The CoP structure and CLE protocols provided opportunity for co-designing joint work, differentiating between technical and adaptive challenges, and using the adaptive leadership framework as anchor for discussion and action. The transfer of practices to school is complex because of the uncertainty and ambiguity that exists in schools and districts. Findings indicate that more research is needed on role of principal supervisors who go against the grain of traditional district office roles with intentionality and create opportunities for high school principals to develop their professional capital as adaptive leaders. That requires a district commitment to redefining the role of supervisor if the supervisor is to fully support site leadership.
Keywords: principal supervisor; adaptive leadership; community learning exchange; Educational leadership; High school principals; School administrators